STRATEGY "UZBEKISTAN-2030" - A HUNDRED STEPS IN THE CONSTRUCTION OF A NEW UZBEKISTAN - t.f.n., Yusupov Rasuljon Malikovich; Son of Numanov Mansurbek Nasirjan (Galaxy International Interdisciplinary Research Journal, 2023)
We aim to be among the “Top” countries of the world by the level of development, and to achieve this goal, we will need a well-developed program. For the development of this program, experts and general public opinion were studied, and many of the proposals received were considered. The Uzbekistan-2030 strategy was developed, taking into account the problems, shortcomings and possible problems and shortcomings in the future. In this regard, the decree “on the strategy of action” was signed by our honored President Shavkat Miromonovich Mirziyoyev on September 11, 2023. It began with the words: "In a referendum held on April 30, 2023, the Constitution of the Republic of Uzbekistan in the new edition was adopted by Universal vote the fact that it was made served to strengthen the constitutional framework for the establishment of a new Uzbekistan.The presidential election held in accordance with the Constitution of the new edition once again testifies to the full support of our people for the political maturity of our society, the reforms that are being carried out towards the establishment of a new Uzbekistan. At the same time, under the updated constitutional and legal conditions, it is required to improve the main directions of the development of our country and bring the large-scale reforms carried out to a new level.”[1]